Analysis of the welfare gap among smallholder palm oil farmers in two scheme farming management: A case study in Lampung province, Indonesia - Lestari, Dyah Aring Hepiana; Fitriani, Fitriani; Prasmatiwi, Fembriarti Erry; Sayekti, Wuryaningsih Dwi; Lestari, Fitri Yuni (Asian Journal of Agriculture and Rural Development, 2025)
This paper aims to analyze the level of welfare of palm oil farmers and the factors that influence it. The research design employs a survey method. Indonesia smallholder palm oil farmers face complex welfare issues. The study employed a survey-based research design. Farmer’s sampling involved 594 palm oil farmers. Quantitative methodology with an ordinal logit regression model is applied to determine the welfare factors. The welfare analysis is carried out by household expenditure approach. The findings reveal the fact that the majority of smallholder palm oil farmers, whether with independent or partnership patterns, are prosperous. The independent pattern has a higher chance of improving welfare. The household prosperity is determined by the variables age, education, number of family members, land cultivated, palm oil income, household income, and cultivation patterns. The direct connection between farmers and the palm oil industry supply chain in the form of cooperation patterns and factory supply guarantees is a basic prerequisite in ensuring improvements in the level of farmers’ income. The practical implication recommends that strengthening farmers in the upstream production line is a precondition in developing the Indonesian sustainable palm oil industry. The synergy among stakeholders in the fair business value chain framework should start from strengthening farmers in the upstream production line.